Similarities and Unique Homogeneity of Certain Letters of Brahui and Balochi Language - Yousaf, Muhammad; Sani, Liaquat Ali; Shawani, Shabeer Ahmed (Makhz (Research Journal), 2024)
Brahui and Balochi, the predominant languages in Balochistan, share profound linguistic and cultural ties rooted in ancient history and geography. The Rakhshani dialect, particularly influenced by Balochi, is geographically surrounded by Balochi on three sides (West, East, and North-East), fostering linguistic convergence. Beyond geographical influences, these languages exhibit striking similarities in vocabulary, phonetics, and syntax. Dr. Abdul Razzaq Sabir asserts that the mutual influence between Brahui and Balochi extends structurally and phonetically. Both languages not only share a common syntax formation but also display semantic connections, distinguishing them from other regional languages. Remarkably, the phonetic resemblance is evident in the shared sounds, making their phonetic structures notably similar. While sharing a common alphabet, Brahui and Balochi maintain distinctive letters and sounds that contribute to their unique linguistic identity. Brahui, in particular, boasts a special letter and sound unparalleled in the region. The establishment of a unified Roman alphabet for both languages further underscores their linguistic interconnectedness, surpassing ties with other languages in the area. Notably, both Balochi and Brahui feature a distinct treatment of "Article" and share the same pronunciation of Arabic sounds. These linguistic nuances contribute to the remarkable linguistic closeness between Brahui and Balochi, setting them apart in the rich tapestry of languages in the region.